High-Volume Return Premium on the Warsaw Stock Exchange: evidence, drivers, and strategy design - Sieradzan, Olga; Wójtowicz, Tomasz (Wydawnictwa AGH, 2026)
This paper investigates the High-Volume Return Premium (HVRP) on the Warsaw Stock Exchange from 2002 to 2023. Building on prior research, it tests whether an unusually high trading volume predicts short-term return anomalies. Using daily data and long-only strategies based on relative trading volume, the study confirms the existence of the HVRP, with the strongest effects observed over one-day horizons, particularly for mid-cap and low-priced stocks. The premium weakens with longer holding periods and lower trading activity. These findings indicate that trading volume carries predictive information in an emerging market context and that volume-based signals can generate exploitable short-term return patterns. However, practical constraints such as transaction costs may limit the real-world profitability of such strategies.
Keywords: trading volume; emerging markets; trading strategy